Old Spanish Trail - Compton, Ralph (New York, N.Y. St. Martin's Paperbacks, 1998)
The ranchers riding with Rand Hayes cross the Mojave Desert to confront the hardships of a brutal land, a hostile Ute nation, and the mysterious territory of California in their attempts to drive the cattle to market.
91369
Keywords: Cattle drives; Western stories; Old Spanish Trail; Western stories